Effect of Centella asiatica Leaves on Gastric Ulcer in Rats - Mariska, Ester; Sitorus, Trully D.; Rachman, Januarsih A. (Althea Medical Journal, 2015)
Â Â Background: Gastric ulcer is disruption of gastric mucosal integrity due to lack of smaller defensive factors (e.g. mucus levels) than gastric aggressive factors. Centella asiatica is a traditional medicine that contains triterpenoids and flavonoids. The objective of this study was to analyze the effect of ethanol extract of Centell aasiatica leaves for preventing gastric mucus level reduction of aspirin-induced gastric ulcer model in rats and compared it to misoprostol.Methods: An experimental laboratory study using 24 rats that were divided into 4 groups. Group I (negative control) received carboxymethy cellulose (CMC) solution, group II (positive control) received CMC and aspirin 450mg/kg, group III (tested group) received Centella asiatica 400 mg/kg and aspirin 450 mg/kg, group IV (compared group) received misoprostol 72Î¼g/kg and aspirin 450mg/kg for three days. Then the rats were laparatomied and their gastric mucus levels were measured. The results were statistically analyzed by Independent T-test.Results: The mean levels of gastric mucus of group I, II, III, IV, respectively were 0.112; 0.035; 0.537; 0.455 optical densities per gram of tissue. The statistical test suggested a significant difference between the positive control group and tested group. Moreover there is no significant difference between the tested group and compared group.Conclusions: Centella asiatica leaves can prevent gastric mucus level reduction of aspirin-induced gastric ulcer model in rats and has similar effect in gastric mucus level with misoprostol.Keywords: Centella asiatica, gastric mucus, gastric ulcer, misoprostolDOI: 10.15850/amj.v2n1.444Â